⁠AI vs Human Creativity: Are Machines Generating Better Ideas? - Fatima Naveed; Iftikhar Alam Khan; Rafia Muhammad Murtaza; Mary Gella; Arshiya Subhani (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
Aim: The study aims to investigate the role of AI in creative processes. It examines whether AI-generated ideas outperform human-generated ideas in terms of originality, quality and preference. The study’s goal is to shed information on AI’s ability to function as a creative partner in order to enhance and increase human creativity. It focuses on evaluating and comparing AI-generated ideas to human-generated ideas to evaluate whether AI produces better ideas or not. Methodology: A mixed method approach was followed, using both qualitative and quantitative methods, i.e, experimentation and an online survey. The experiment initially comprised two groups of students: AI users and Non-AI users. Both groups were asked to generate ideas regarding a single prompt. These ideas, shuffled and combined into a single list was then presented to a third neutral group unknown to which ideas were AI generated and which were not. This group was then asked to vote for the top 5 ideas. Furthermore, an additional quantitative survey was also taken to further studies regarding AI usage and over-reliance concerns. Findings: The experiment resulted in 52.9% (98) votes were given to AI generated ideas while 47.3% (87) votes were given to ideas generated by humans. Furthermore, the idea that received the most votes was generated by AI. The top 5 most voted concepts have an equal number of AI and Non-AI generated results. Although both received the same top 5 score, it demonstrates that AI can develop creative and original ideas preferred by humans. Whereas the 5 least voted idea list comprised 3 ideas generated by humans and only 2 generated by AI. Additionally, the survey results indicated that approximately 62% of respondents were concerned about generative AI posing long-term risks to human creativity. Novelty & Implications: This study investigates the role of artificial intelligence (AI) in ideation and creative processes, as well as its collaborative interaction with humans. It studies if AI generates greater ideas than humans and makes comparisons between the two. Unlike earlier research, which has focused on AI’s applications in academics, businesses, and other sectors, this study focuses on AI’s function in creative ideation. The results indicate AI’s positive impact, with AI-generated concepts receiving more votes overall. However, respondents also showed concern about the long-term effects of AI overuse on human creativity. The study suggests a balanced collaboration between AI and human minds to maximise creative potential.